Secondary Metabolites in Basil, Bio-Insecticide, Inhibition Effect, and In Silico Molecular Docking against Proteolytic Enzymes of the Red Palm Weevil (Rhynchophorus ferrugineus) - Hossam Moustafa Darrag; Hani Taher Almuhanna; Emadaldeen Hamad Hakami (Plants, 2022)
The purpose of this work was to determine the secondary metabolites generated by O. basilicum cell suspensions, as well as their insecticide and inhibitory activity against R. ferrugineus. The growth kinetics with inoculation Verticillium dahliae were determined and identified using LC-MS. Determination of total phenolic components (TFC), flavonoids (TF), and condensed tannins (TCT) were measured. Insecticidal activity of O. basilicum extract against R. ferrugineus (larva and adult) and proteolytic enzymes activity were assessed (in vitro and in vivo). The O.basilicum extract had an LC50 of 1238 µg/mL and an LD50 of 13.4 µg/larva. The LC50 of chicoric acid, ursolic acid, salvigenin, quercetin-3-O-rutinoside, rosmarinyl glucoside, and nepetoidin B demonstrated activity at an LC50 of 1132, 1167, 1189, 1214, 1275, and 1317 µg/mL, respectively. Chicoric acid, salvigenin, nepetoidin B, and rosmarinic acid demonstrated an LD50 activity of 10.23, 11.4, 11.9, and 12.4 µg/larva, respectively. The active extract of O. basilicum inhibited total protease, trypsin-like serine proteinases, elastase, cysteine, and metalloprotease activity with an IC50 (in vitro) of 119.4, 91, 102.4, 76.4, and 52.4 µg/mL, respectively. In silico studies of compounds were conducted, such as molecular docking and ADMET analysis. The study proposes using an efficient cell suspension technique to produce O. basilicum extract containing active secondary metabolites and accessible using as bio-insecticide.